Cr‐Doped La‐Ni‐O Catalysts Derived from Perovskite Precursors for CH4‐CO2 Reforming under Microwave Irradiation. Issue 8 (29th June 2016) - Odedairo, Taiwo; Ma, Jun; Chen, Jiuling; Zhu, Zhonghua
Abstract: The nickel catalysts derived from Cr‐doped LaNiO3 perovskite‐like precursors were characterized by X‐ray diffraction, high‐resolution transmission electron microscopy, temperature‐programmed oxidation, temperature‐programmed reduction, and X‐ray photoelectron spectroscopy. Their catalytic performance in CO2 reforming of methane under microwave irradiation was investigated. It was found that the structure and morphology of the oxide composites in this research were influenced by the ratio of Ni and Cr, and the mismatch of La 3+, Ni 3+, and Cr 3+ may cause phase segregation. The catalytic performance of the Ni catalysts is dependent on the oxygen mobility of the perovskite oxide matrix, the content of the reduced Ni 0, and the content of the remaining perovskite structure. The mobile oxygen in the perovskite matrix in the catalyst may enhance the conversion of CO2 during the reaction. Abstract : Nickel proved to be suitable to replace noble metals as catalyst for dry reforming of methane, but it suffers from deactivation due to formation of unreactive carbons on the catalyst surface. To improve the stability of high‐dispersed Ni particles, a Cr‐doped LaNiO3 perovskite‐like structure was employed as catalyst precursor in which Ni 3+ sites will be partially substituted with Cr 3+ .